Efficient Wastewater Treatment via Aeration Through a Novel Nanobubble System in Sequence Batch Reactors - Ahmadi, Mehrdad; Doroodmand, Mohammad Mahdi; Nabi Bidhendi, Gholamreza; Torabian, Ali; Mehrdadi, Nasser (Frontiers in Energy Research, 2022)
The aerobic wastewater treatments depend on the aeration. Hence, the size of the bubbles used in the aeration system may play a crucial role in this regard. This study attempted to investigate the effects of aeration bubble size on wastewater treatment efficiency of a “sequence batch reactor” (SBR) system at a laboratory scale using a novel designed fine/nanobubble forming instrumentation system. Based on the presence of microorganisms in the stationary phase, chemical oxygen demand removal efficiency on the 15th day (80.0 and 95.0%) was majorly better than on the 10th and 15th days in fine and nanobubble aeration systems. Moreover, with increasing sludge age, the “sludge volumetric index” (SVI) increased up to 170.0 ml g−1 on the 15th day. In addition, sludge rate and F/M ratio were much higher and expressively less in the nanobubble system rather than in the fine-bubbles system in which sludge was majorly denser. Therefore, the sludge was more easily deposited and the percentage of dry sludge was higher compared with the fine-bubble system. Thus, oxygen and specific oxygen uptake rate consumption were significantly reduced. The efficiency of the phosphorus removal was estimated to be between 54.0–60.0% for nanobubble aeration, compared to the general systems such as the SBR (10–20%) under similar conditions. In addition, the efficiency of the nitrogen removal in the nanobubble aeration system with different densities of 40.0, 50.0, and 60.0 ml g−1 was found as 99.0%, relatively higher compared to fine bubble with 96.0% nitrogen efficiency. In conclusion, a nanobubble aeration system could give considerably promoted efficiencies in all terms of the tested treatment effective parameters.